Implementasi Digital Government Services pada Bidang Pendidikan di Pemerintah Propinsi DIY - Sri Wahyuni; Bagus Indarwanto (Magister Administrasi Publik, 2008)
The study was focused on the implementation of digital government services in education in DIY Province, especially how far the implementation of the program goes, how effective teh program can solve the gap of quality in education and what kinds of constraints were faced in the process of the program implementation. The implementation process was explained with several aspects: e-leadership, human resources, infrastructure, business environment, and learning gateway portal development.The result of the study showed that the e-leadership was not owned yet by all leaders at all level. From the aspect of infrastructure development, it can be seen that the capacity of the Government of DIY Province is still relatively low. The allocation of budget from APBD of DIY Province was not comprehensive and suitable yet, causing a problem in providing the infrastructure of computer laboratories for schools in DIY Province. The human resources development was not yet adequate because the result of the trainings couldn't fulfill the competency needed for managing the DIY Learnng Gateway Service. The growth of internet cafes need a regulation that protects the internet user (especially the pupils) from the negative material such as pornography. The constraints faces in the implementation of the program were: it was difficult to coordinate crossed-functionally, the competency of the teachers was relatively low, the infrastructure and the budget were inadequate, and the licenses for the Internet Service Providers in Indonesia were very various.Strating from the result of the study, it is recommended that it is necessary to develop a stronger e-leadership not only for local leaders but also for the schools that provide the virtual school service, to provide an accurate data about the schools that need computer laboratories, to give more applicable training for teachers and to provide the internet at schools as soon as possible through various programs such as Komputer Murah, Laptop Murah and so on.